2021
DOI: 10.3343/alm.2021.41.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Guided Risk Assessment for Acute Kidney Injury: Time for Clinical Implementation?

Abstract: Acute kidney injury (AKI) is a common and serious complication in hospitalized patients, which continues to pose a clinical challenge for treating physicians. The most recent Kidney Disease Improving Global Outcomes practice guidelines for AKI have restated the importance of earliest possible detection of AKI and adjusting treatment accordingly. Since the emergence of initial studies examining the use of neutrophil gelatinase-associated lipocalin (NGAL) and cycle arrest biomarkers, tissue inhibitor metalloprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 72 publications
(130 reference statements)
0
50
0
5
Order By: Relevance
“…We note that our case study data were somewhat artificial, with the same number of thresholds and same requirement for each threshold (that gave 95% sensitivity, 95% specificity, and maximized the Youden index, respectively) in all primary studies. This specific setting resulted from the original study's aim to identify urinary and plasma NGAL cut‐off concentrations with high sensitivity or high specificity to complement the identification of patients at high kidney risk in clinical research and practice (Albert et al., 2020b, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We note that our case study data were somewhat artificial, with the same number of thresholds and same requirement for each threshold (that gave 95% sensitivity, 95% specificity, and maximized the Youden index, respectively) in all primary studies. This specific setting resulted from the original study's aim to identify urinary and plasma NGAL cut‐off concentrations with high sensitivity or high specificity to complement the identification of patients at high kidney risk in clinical research and practice (Albert et al., 2020b, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made in the development of new biomarkers to diagnose and manage AKIs that go beyond the current AKI definition/staging criteria [ 36 ]. Importantly, biomarker-based improved risk assessment after cardiac surgery may guide timely initiation of effective nephroprotective measures addressing hemodynamic and medication adjustments after cardiac surgery [ 37 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in serum creatinine concentration (SCr) and a reduction in urine output are the current diagnostic markers for VAKI [5,6,10]; however, these traditional markers of kidney function might not be sensitive to kidney damage, and their changes lag several days behind actual changes in glomerular filtration rate (GFR) [11]. Recent studies have shown that novel biomarkers of kidney damage, including kidney injury molecule-1, neutrophil gelatinase-associated lipocalin, liver-type fatty acid-binding protein, and interleukin-18, increase before SCr [12][13][14][15][16]. However, it is unclear whether these biomarkers could reveal the different AKI-inducing mechanisms and conditions, such as toxicity, nephron obstruction, ischemia, and inflammation [10,11].…”
Section: Introductionmentioning
confidence: 99%